Traitors [videorecording (DVD)] - Gullette, Sean; Ben Acha, Chaimae; Issami, Soufia; Zeguindi, Mourade (Film Movement, 2015)
To keep her parents from being evicted and fund her Clash-inspired punk band, Malika takes a job smuggling drugs over the mountains. Her partner in the run is a world-weary veteran drug mule, who unexpectedly wins Malika's sympathy.